ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN REMITAN OLEH PEKERJA MIGRAN NONPERMANEN SEKTOR INFORMAL DI KELURAHAN JIMBARAN - Purnami, Ni Kadek Ayu; Sudibia, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.07.TAHUN.2023, 2023)
The purpose of this study was to analyze the effect of marital status, number of family dependents and allocation of working hours on the income of non-permanent migrant workers, analyze the effect of marital status, number of family dependents, allocation of working hours and income on remittances for non-permanent migrant workers, and analyze the indirect effect of marital status. , number of family dependents and allocation of working hours to remittances through non-permanent migrant income. The sample taken is 121 non-permanent migrants who work in the informal sector in Jimbaran Village. The sampling method used was purposive sampling combined with accidental sampling using path analysis. The results of this study indicate that marital status, number of family dependents and allocation of working hours have a positive and significant effect on income. Marital status, number of dependents, allocation of working hours, and income have a positive and significant impact on the provision of remittances for non-permanent migrant workers. Marital status, number of family dependents, and allocation of working hours have an indirect effect on the provision of remittances for non-permanent migrant workers through income.